Bride-Wealth: Is There Respect for Women in Manggarai, Eastern Indonesia? - Yohanes Servatius Lon; Fransiska Widyawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
This study explores the perspective of women in Manggarai, Flores Island in Indonesia, and the communaltraditional concept of bride-wealth as a symbol of respect for women. This study uses a qualitative approach by interviewing forty women, both married and unmarried. The respondents were asked their opinion regarding their imagination about bride-wealth and its influence on their courtship, engagement, wedding, and married life. The results indicated the presence of a gap between the social imagination of bride-wealth and the women’s true experience. Most respondents stated how bride-wealth had strained their relationship and become a source of worry. The study therefore argues that bride-wealth as a sign of respect for women in Manggarai is merely a social imagination ingrained into the women’s expectations. The study also indicates that education has changed the status of women and enables them to be independent.